Hello, summer - Andrews, Mary Kay, 1954- (New York : St. Martin's Press, 2020)
After ten years of hard work, Conley is about to take a fancy new position at a New York City newspaper. Then she discovers that her new job is suddenly gone, disappearing overnight along with her dreams of a bright future in a big city. With a sinking feeling in her gut, Conley ends up in the last place she ever wanted to be: The Beacon, a small town newspaper. The paper is now reluctantly run by her brother Garret, whose own dreams of being a lawyer were put on hold with the death of their father. Covering a sleepy beach town with church news and the local funeral home director dictating the day$1 (Bs obituaries to her over the phone isn$1 (Bt exactly every reporter$1 (Bs dream, and to make matters worse, she and her brother see eye to eye on almost nothing. s
Keywords: Newspaper employees -- Fiction; Women journalists -- Fiction; Reporters and reporting -- Fiction; Homecoming -- Fiction; Brothers and sisters -- Fiction; Journalists -- Fiction; Small cities -- Fiction; Veterans -- Fiction; Politicians -- Death -- Fiction; Families -- Fiction; Florida Panhandle (Fla.) -- Fiction; Romance fiction; Domestic fiction